The Impact of Artificial Intelligence on the Activities of Hospitality Organizations - Dr. Mohammed Mohsen Ibrahim Al-Obaidi (Peerian Journals Publishing, 2026)
This study aims to demonstrate the importance of artificial intelligence in the hotel and hospitality industry. The study addresses the question of whether a strategy is being implemented in Iraq within the hospitality and hotel sector, and the extent of its impact on the operations and activities of hospitality organizations and the tourism sector in general. The study aimed to demonstrate the importance of applying artificial intelligence technologies in the tourism andhospitality sectors. The descriptive, analytical, and exploratory approach was followed in presenting the concepts and arriving at the results through the use of peer-reviewed scientific journals and websites . The importance of this study stems from the growing significance of artificial intelligence (AI) in hospitality establishments, which impacts their operations and performance AI is considered crucial as it is one of the most important modern tools and a major source of revenue for countries worldwide. The study concluded that its use effectively contributes to boosting tourism
Keywords: Artificial intelligence; hotel establishments; hospitality; tourism